PENGARUH METODE MATEMATIKA GASING (GAMPANG, ASIK DAN MENYENANGKAN) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IV SEKOLAH DASAR - Syauqina Putri, Dinda; Herli Sundi, Venni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This thesis is motivated by the low level of students' understanding of mathematical concepts, particularly in the topic of fractions among fourth-grade elementary school students. The purpose of this study is to determine the effect of the GASING (Easy, Fun, and Enjoyable) Mathematics method on the conceptual understanding of mathematics among fourth-grade students at SD Negeri Meruyung. The research was conducted at SD Negeri Meruyung, located in Limo District, Depok City. The population of this study consisted of all fourth-grade students, with a total sample of 64 students. The instrument used was a post-test designed to measure students’ conceptual understanding of mathematics. This research employed a quantitative approach using an experimental method. The results indicated a significant effect of the GASING method on students’ mathematical conceptual understanding. This was evidenced by the results of the Independent Samples t-Test using SPSS 26, which showed a significance value (Sig. 2-tailed) of 0.000 < 0.05. Based on the Levene’s Test for homogeneity, the results indicated that the variances between the two groups were different. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be concluded that the use of the GASING Mathematics method significantly influences the conceptual understanding of mathematics among fourth-grade students at SD Negeri Meruyung in the 2024/2025 academic year.